(untitled) (Journal of Pathology of Nepal, 2020)
In an ongoing pandemic it is critical to track the virus, understand pathogenesis and epidemiology, manage the cases and suppress transmission that requires effective laboratory testing. In December 2019, a cluster of patients with a novel coronavirus was identified in Wuhan, China. Initially tentatively named 2019 novel coronavirus (2019-nCoV), the virus has now been named SARS-CoV-2 by the International Committee of Taxonomy of Viruses (ICTV). This virus can cause the disease named coronavirus disease 2019 (COVID-19).